Contour maps of mechanical properties in ternary ZrB2SiCZrC ceramic system. (October 2015) - Liu, Hu-Lin; Liu, Ji-Xuan; Liu, Hai-Tao; Zhang, Guo-Jun
Graphical abstract: Abstract: Monolithic ZrB2, ZrB2 SiC, ZrB2 ZrC and ZrB2 SiCZrC were prepared by hot pressing in ternary ZrB2 SiCZrC system. They exhibited different microstructural features. Grain sizes of each phase were smaller in the ternary composites. Contour maps of mechanical properties were also plotted in ZrB2 SiCZrC ternary diagram based on experiments and software fitting. They established the relationships between chemical composition and properties in a visual way. Young's Modulus and Vickers hardness had linear relationships with composition, while the evolution of the strength and toughness was complicated.